Pendidikan Karakter Religius Anak Yatim Piatu di Panti Asuhan Al Hasyimiyah Bandung Diwek Jombang - Abdul Natsir; Zainul Abidin; Irfan Zidni (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
This study aims to determine the Religious Character Education system for Orphans at the Al Hasyimiyah Bandung Diwek Jombang Orphanage. This study is a qualitative research type, taking the background of the Al Hasyimiyah Bandung Diwek Jombang Orphanage. Data collection was carried out by means of interviews and observations. While the data analysis used inductive analysis techniques, which were carried out by summarizing specific data, then describing and concluding in general. The results of the study showed that the religious character education system for orphans at the Al Hasyimiyah Bandung Diwek Jombang Orphanage was carried out by training children's independence, getting children used to being disciplined in worship, tadarus al-Qur'an, tahfidzul Qur'an and other diniyah activities. All of this was done through a coaching stage which included: habituation, role models, advice and punishment. Keywords: Orphanage; Orphans; Religious Character